2021
DOI: 10.4209/aaqr.210220
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Leakages through Fault Zones: Potential Implications for the Long-term Integrity of Geological Storage Sites

Abstract: Carbon sequestration has recently become more widely recognized as a potential means of reducing atmospheric carbon dioxide levels. Understanding the tectonic relationship of carbon dioxide discharges and the sealing behavior of faults is conducive for predicting the long-term integrity of geological storage formations. Of primary concern is the influence of crustal deformation on the carbon dioxide leakage through fault zones during large-scale underground injection. This paper examines a record of carbon dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…With the injection of CO 2 into the subsurface and its long-term storage, the stress field and chemical field in the layer change, triggering a series of changes in geological factors that affect the stability and safety of long-term storage of CO 2 . Yang Duoxing et al found that carbon dioxide-leakage levels and crustal tilt changes vary systematically through time and are highly correlated, indicating increased degrees of carbon dioxide degassing from the fault zone [12]. Xu Lifeng et al conducted five groups of supercritical CO 2 leakage experiments at different initial CO 2 temperatures to study the mechanism of internal and external strain differences caused by the phase transition of supercritical CO 2 leakage along faults [13].…”
Section: Introductionmentioning
confidence: 99%
“…With the injection of CO 2 into the subsurface and its long-term storage, the stress field and chemical field in the layer change, triggering a series of changes in geological factors that affect the stability and safety of long-term storage of CO 2 . Yang Duoxing et al found that carbon dioxide-leakage levels and crustal tilt changes vary systematically through time and are highly correlated, indicating increased degrees of carbon dioxide degassing from the fault zone [12]. Xu Lifeng et al conducted five groups of supercritical CO 2 leakage experiments at different initial CO 2 temperatures to study the mechanism of internal and external strain differences caused by the phase transition of supercritical CO 2 leakage along faults [13].…”
Section: Introductionmentioning
confidence: 99%